Effects of the Chinese medicine Yi Shen Jian Gu granules on aromatase inhibitor-associated musculoskeletal symptoms: A randomized, controlled clinical trial. (February 2018) - Peng, Nan; Yu, Mingwei; Yang, Guowang; Fu, Qi; Xu, Yongmei; Yu, Jie; Liu, Qiang; Li, Chen; Xu, Weiru; Zhang, Yi; Ma, Cong; Yang, Lin; et al.
Abstract: Aromatase inhibitor-associated musculoskeletal symptoms (AIMSS) are prevalent among patients on AI therapy, which leads to a lower quality of life and poor adherence to AI treatment. We evaluated whether Yi Shen Jian Gu granules (YSJG) is effective and safe to relieve AIMSS in patients with breast cancer. Eligible participants were randomly assigned to the YSJG group or the placebo group. Both groups had a 12-week treatment period and a 12-week follow-up period. Brief Pain Inventory-Short Form (BPI-SF), Western Ontario and McMaster Universities Osteoarthritis (WOMAC) Index, and the Modified Score for the Assessment and Quantification of Chronic Rheumatoid Affections of the Hands (M-SACRAH) were obtained at baseline and at 4, 8, 12 and 24 weeks. Of 146 participants enrolled, 84 were randomly assigned, and 77 were evaluable at 12 weeks. Baseline characteristics were comparable between two groups. The primary outcome was the differences in mean BPI-SF scores at 12 weeks. The worst pain scores decreased by 3.10 points (50.2%; 95% CI, 2.50 to 3.65) for YSJG group compared with a 1.63-point decrease (26.9%; 95% CI, 3.86 to 4.97) for the placebo group ( P = 0.001). Significantly improvements were also observed for the WOMAC and M-SACRAH. Possibly YSJG-related side effects were grade 1 nausea (10%) and grade 2 diarrhea (2%). Serum follicle-stimulating hormone and serum estradiol were kept in the postmenopausal range before and after YSJG treatment. Patients with AIMSS treated with YSJG granules had significant improvements in musculoskeletal symptoms. YSJG is effective, safe and well-tolerated in managing AIMSS. Trial registration: ISCTN: ISRCTN06129599 (assigned 14 August 2013). Highlights: Around half of patients on AI therapy experience musculoskeletal symptoms, which have become a major clinical issue. Effective management of AIMSS still awaits disclosure. Compared to similar studies, our trial has the following advantages. First, our study design is a multicenter, randomized, double-blind, placebo-controlled clinical trial. Second, the procedure of our research was supervised by an independent third-party clinical research center. Third, we observed a 3.10 decrease in BPI-SF for YSJG arm, which was greater than that reported in other similar studies. Additionally, the maintenance of symptomatic improvement during follow-up period implied long-term effects of YSJG. In conclusion, YSJG granules is effective, safe and well-tolerated in managing AIMSS.